2022
DOI: 10.1186/s12864-022-08487-8
|View full text |Cite
|
Sign up to set email alerts
|

Multi-trait genomic prediction using in-season physiological parameters increases prediction accuracy of complex traits in US wheat

Abstract: Background Recently genomic selection (GS) has emerged as an important tool for plant breeders to select superior genotypes. Multi-trait (MT) prediction model provides an opportunity to improve the predictive ability of expensive and labor-intensive traits. In this study, we assessed the potential use of a MT genomic prediction model by incorporating two physiological traits (canopy temperature, CT and normalized difference vegetation index, NDVI) to predict 5 complex primary traits (harvest in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 67 publications
(113 reference statements)
3
6
1
Order By: Relevance
“…As observed in other studies ( Aroujju et al 2020 ; Shahi et al . 2022 ), the MT methods generally did not present a better performance than ST did when observations for the correlated indicator trait were omitted in the testing set (CV1).…”
Section: Discussionsupporting
confidence: 88%
“…As observed in other studies ( Aroujju et al 2020 ; Shahi et al . 2022 ), the MT methods generally did not present a better performance than ST did when observations for the correlated indicator trait were omitted in the testing set (CV1).…”
Section: Discussionsupporting
confidence: 88%
“…Instead, data from professional testers and biochemical traits from analytical techniques in the late stages can be used to train the GS model in the nursery stage. Genotyped seedlings could be selected for multiple traits such as tea quality and yield simultaneously using a multi‐trait GS model framework and a selection index (Shahi et al., 2022). Selection for better tea quality could thus begin at the earliest stage, where variation in quality traits is greater.…”
Section: Discussionmentioning
confidence: 99%
“…The PA of the single-trait rrBLUP method of DTF, HIR, and PHT in MAGIC DHIs was moderate to high (Table 3), while employing multiple-trait GP models can increase PA even further for MAGIC DHIs. Using multitrait as multiple response variables in the GP models, the PA of low-heritability traits (<0.2) can take advantage of leveraging the genetic correlation with high-heritability traits (Jia and Jannink, 2012;Gaire et al, 2022;Shahi et al, 2022). In addition, synthetic populations generated by less than eight parents can yield high PA for GS (Schopp et al, 2017).…”
Section: Applications Of Gs In Dhis Derived From Multiple Families An...mentioning
confidence: 99%
“…However, lines in breeding programs are usually evaluated for multiple traits. Simulation and empirical studies revealed that implementing multi-trait response variables in GP models has a higher prediction ability than single-trait GP models by leveraging estimates of covariance among genetically correlated traits (Jia and Jannink, 2012;Bhatta et al, 2020;Gill et al, 2021;Cappa et al, 2022;Shahi et al, 2022). The benefits of using multi-trait models are more pronounced for traits with low heritability and phenotypic traits that require costly measurements (Guo et al, 2014;Gaire et al, 2022).…”
Section: Introductionmentioning
confidence: 99%